Impact of pandemic COVID-19 on the E-banking customer behavior: Case of Indonesia - Pramuditya, Fani; Azis, An Nisa Febri (Universitas Ahmad Dahlan, 2024)
This study aims to evaluate the factors affecting customers' acceptance and use of the internet and mobile banking during the COVID-19 pandemic. In Indonesia, the COVID-19 epidemic has encouraged residents to utilize other payment methods rather than cash, which easily spreading the virus. Internet and mobile banking are examples of technological innovations which can assist banking customers during the COVID-19 pandemic since it is safer, easier to access, and needs less human interaction. This paper utilizes a Unified Theory of Acceptance and Use of Technology (UTAUT) Model to assess consumers' intentions to use the internet and mobile banking. Previous research discussed the mobile banking adoption during the Covid-19 in various fields. Therefore, it is important to analyze the mobile banking intention and behavior in Indonesia. The data collected from questionnaires are used to evaluate the conceptual model, which shows the relationship between UTAUT constructs, performance expectancy, experience expectancy, and social influence. From 158 questionnaires with diverse demographic backgrounds gathered, we found that effort expectancy, performance expectancy, and social influence have a positive impact on the behavioral intention. Furthermore, it found that behavioral intention and facilitating conditions have influence on the using behavior. These results give a suggestion to both the banking industry and government to improve their mobile banking system to improve financial inclusion.